EXPLORING TEACHERS’ PERCEPTION OF SUGGESTING ANGLOMANIACY IN TEACHING ENGLISH TO YOUNG LEARNERS - Azra Batrisyia Sabrina; Achmad Ramadhan (VISION, 2026)
Teaching English to young learners generates many benefits, because children have a special capability to learn new knowledge effortlessly. However, teaching them could be challenging with unsupported equipment. This research aims to explore the utilization of a digital tool, Anglomaniacy, in young learner classrooms from the teachers’ perspective, to determine whether it can serve as a supporting tool that enhances learners’ English proficiency skills, such as vocabulary, pronunciation, speaking, reading, and others. This research was conducted online with three teachers from three primary grades in the Indonesia Teaching Community (ITC). The teachers were observed and asked to complete a questionnaire regarding their experience with utilizing Anglomaniacy in their classrooms. Thus, the data were collected through observations and a questionnaire created with Google Forms and shared via WhatsApp. Furthermore, the data of this phenomenological study were analyzed by applying Cresswell’s steps, including transcribing and coding the data. The findings showed that the three teachers suggest that Anglomaniacy has many benefits for teaching English to young learners, including providing useful features, boosting engagement, and vocabulary enhancement. However, they also explain several limitations while using it, such as limited topics and technical issues. Therefore, this research highlights further studies regarding Anglomaniacy use in Indonesia’s curriculum design.